ANALISIS MAKNA LAFADZ, AL-MUDHAF DAN ISIM YANG BERSIFAT UMUM - Iqna Auliyah; Pathur Rahman; Mohammad Fatah; Miftahul Jannah (AL-BAYAN INSTITUTE, 2022)
This research discusses advanced linguistic principles related to tafsir, specifically regarding lafadz as a vessel of meaning, al-mudhaf as isim al-jami', and nouns that are mentioned individually but indicate a general meaning. Through analysis of various examples in the Qur'an, this article emphasizes the importance of a deep understanding of these terms in the context of interpretation. The study shows that lafadz is not only a linguistic symbol but also a medium that conveys broader and more complex divine messages. By understanding the use of lafadz and terms in the Qur'an, we can uncover deeper meanings, thereby providing a more comprehensive understanding of Islamic teachings and humanity's responsibilities in a larger context.